2012
DOI: 10.1007/s00268-012-1817-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Infection after 46,113 Intramedullary Nail Operations in Low‐ and Middle‐income Countries

Abstract: BackgroundThe fields of surgery and trauma care have largely been neglected in the global health discussion. As a result the idea that surgery is not safe or cost effective in resource-limited settings has gone unchallenged. The SIGN Online Surgical Database (SOSD) is now one of the largest databases on trauma surgery in low- and middle-income countries (LMIC). We wished to examine infection rates and risk factors for infection after IM nail operations in LMIC using this data.MethodsThe SOSD contained 46,722 I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
58
3
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 41 publications
6
58
3
4
Order By: Relevance
“…One likely factor in the impressively low frequency of malalignment in SIGN surgeries is that although the surgery can be performed without fluoroscopic imaging, the majority of the surgeries are performed using some measure of open reduction. Despite the use of adjunctive open reduction, infection rates in SIGN surgeries are within the acceptable norm and are more influenced by fracture characteristics and the use of preoperative antibiotics [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…One likely factor in the impressively low frequency of malalignment in SIGN surgeries is that although the surgery can be performed without fluoroscopic imaging, the majority of the surgeries are performed using some measure of open reduction. Despite the use of adjunctive open reduction, infection rates in SIGN surgeries are within the acceptable norm and are more influenced by fracture characteristics and the use of preoperative antibiotics [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…3 IMN fixation especially has become standard treatment of femoral and tibial shaft fractures resulting in a high rate of union; however, past studies have shown an increased risk of infection for IMN of open fractures when compared to any orthopaedic trauma surgery. [10][11][12][13][14] On the contrary, a study by Avilucea et al found that plating leads to higher rates of nonunion and increases the odds of postoperative complications compared with IMN of open tibial shaft fractures. 15 Im and colleagues similarly found that the plating group was associated with a 23% infection rate compared to a rate of 3% for IMN patients.…”
Section: Introductionmentioning
confidence: 90%
“…Rates in the femur are reported at slightly lower rates (1.5-3.2 %) largely because of the more generous soft tissue envelope and decreased risk of open fracture [ 18 , 19 , 40 , 41 ]. The rate of infection following intramedullary nailing of humerus fractures is similarly low [ 40 ]. There are several well accepted risk factors for infection following intramedullary nailing.…”
Section: Infectionmentioning
confidence: 98%
“…Single or serial thorough debridements are of utmost importance for prevention of deep infection. Delay or lack of peri-operative prophylactic antibiotics also increases the risk of postoperative infection by up to 29 % [ 40 ]. Other risk factors for infection following intramedullary fi xation include lower socioeconomic status [ 40 ], delay in soft tissue coverage/wound closure [ 43 ] and duration of the surgical procedure [ 18 , 42 ].…”
Section: Infectionmentioning
confidence: 99%
See 1 more Smart Citation